2020
DOI: 10.1007/s12640-020-00288-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute Traumatic Brain Injury-Induced Neuroinflammatory Response and Neurovascular Disorders in the Brain

Abstract: Acute traumatic brain injury (TBI) leads to neuroinflammation, neurodegeneration, cognitive decline, psychological disorders, increased blood-brain barrier (BBB) permeability, and microvascular damage in the brain. Inflammatory mediators secreted from activated glial cells, neurons, and mast cells are implicated in the pathogenesis of TBI through secondary brain damage. Abnormalities or damage to the neurovascular unit is the indication of secondary injuries in the brain after TBI. However, the precise mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…For BBB structures damage, an inevitable consequence of BBB breakdown is an increase in the permeability of the damaged endothelium (Bhowmick et al, 2019). Following TBI, the endothelium-associated tight junction proteins JAM-A, ZO-1, occludin, and claudin-5 were down-regulated indicating acute TBI-associated tight junction protein disruption (Evran et al, 2020;Sivandzade et al, 2020;Kempuraj et al, 2021). The studies showed that after animal TBI model, as many as 40% of the pericytes loss the contact of basement membrane within the first hours of the injury (Dore-Duffy et al, 2000).…”
Section: Blood-brain Barrier Breakdown Following Traumatic Brain Injurymentioning
confidence: 99%
“…For BBB structures damage, an inevitable consequence of BBB breakdown is an increase in the permeability of the damaged endothelium (Bhowmick et al, 2019). Following TBI, the endothelium-associated tight junction proteins JAM-A, ZO-1, occludin, and claudin-5 were down-regulated indicating acute TBI-associated tight junction protein disruption (Evran et al, 2020;Sivandzade et al, 2020;Kempuraj et al, 2021). The studies showed that after animal TBI model, as many as 40% of the pericytes loss the contact of basement membrane within the first hours of the injury (Dore-Duffy et al, 2000).…”
Section: Blood-brain Barrier Breakdown Following Traumatic Brain Injurymentioning
confidence: 99%
“…Such inflammatory milieu might potentiate the risk for SI and SB as they have been convincingly shown to be positive correlates of suicidality [58,59]. In this regard, patients with SA exhibit high levels of several inflammatory markers, such as IL-6 and TNF-α [60,61], all of which were found to be elevated in the cerebrospinal fluid of subjects with traumatic brain injuries [57,62]. Chronic progressive head traumas cause axonal damage resulting in pathogenic expression of tau and TAR DNA binding protein 43 (TDP43) proteins and induction of other factors such as neurofilament light polypeptide (NFL), brain-derived neurotrophic factor (BDNF), and serotonin transporter 5-HTTLPR.…”
Section: Neurobiological Hypotheses For the Development Of Suicidalitmentioning
confidence: 99%
“…A major consequence of TBI is direct damage to the cerebral vasculature, leading to hemorrhage, CBF abnormalities, blood–brain barrier (BBB) disruption, and edema 10 12 . These early events are followed by hypoperfusion and compromise of the cerebral microvasculature resulting in capillary stasis, ischemia and hypoxic tissue damage.…”
Section: Introductionmentioning
confidence: 99%